Manajemen Strategi Pendidikan Pondok Pesantren Al-Hasan Banjarsari Ciamis dalam Membina Kedisiplinan Santri di Masa Pandemi Covid-19 - Sa'diah, Dewi; Hamdani, Amin; Mubarok, Ridwan (Tadbir: Jurnal Manajemen Dakwah, 2023)
In the current era, the presence of Islamic boarding schools is very urgent to support the progress of the Indonesian nation. Because the Islamic boarding school system teaches not only religious matters (tafaquh fid din) but also the basics of science and technology, social and cultural boarding schools, al-Karima morals, independence, simplicity, modesty, honesty, togetherness, compassion, discipline, this research aims to determine the formulation and implementation of Islamic boarding school education carried out by kiai at Islamic boarding schools in fostering santri discipline during the Covid-19 pandemic and to evaluate changes in santri behavior in fostering santri discipline at Islamic boarding schools. This research uses a descriptive method with a qualitative approach. The results of this research show that the formulations carried out by kiai in Islamic boarding schools in fostering student discipline during the COVID-19 period include a. Formulate the vision, mission, goals, and educational programs of the Islamic boarding school as expected; b. Create disciplinary regulations and guidelines for violations and punishments, and determine a schedule for student disciplinary activities. The implementation of Islamic boarding school education carried out by kiai includes a. providing direction, role models, advice, good example, motivation, enthusiasm, leading throughout students' disciplinary education, and communicating well. Evaluation of changes in student behavior in fostering student discipline includes: Changes in students' behavior occur because they have habits that have been ingrained in them with their awareness and are always guided by their kiai, mentors, ustadz, and ustadzah.